Effect of dietary vitamin D levels on growth, serum biochemical parameters, lipid metabolism enzyme activities, fatty acid synthase and hepatic lipase mRNA expression for orange‐spotted grouper (Epinephelus coioides) in growth mid‐stage. (7th January 2021) - He, Shuqing; Ding, Mingyan; Watson Ray, Gyan; Yang, Qihui; Tan, Beiping; Dong, Xiaohui; Chi, Shuyan; Liu, Hongyu; Zhang, Shuang
Abstract: This study was conducted to evaluate the effect of dietary vitamin D (VD) levels on growth, serum biochemical parameters and lipid metabolism in the liver for orange‐spotted grouper ( Epinephelus coioides ). The fish (initial weight 81.50 ± 0.05 g) were fed diets containing different VD levels (i.e., 0, 500, 1000, 2000, 4000 and 10, 000 IU/kg) for 10 weeks. With the increasing level of VD, the weight gain rate (WGR) and the specific growth rate initially increased and then decreased, and the feed conversion ratio significantly decreased in fish supplemented with dietary VD of 1000 IU/kg compared with control group ( p  < .05). Diet with VD 1000 IU/kg significantly ( p  < .05) increased the whole‐body crude protein. In the liver, the lipid content decreased while the VD deposition increased significantly ( p  < .05). VD had significant ( p  < .05) positive effects on the serum biochemical parameters and lipid metabolism enzyme activities in the liver. Moreover, VD supplementation significantly inhibited the FAS mRNA expression and promoted the HL mRNA expression ( p  < .05). The broken‐line model of the WGR corresponding to the VD levels indicated that the optimal supplement of dietary VD was 750.19 IU/kg. Diet with VD supplement from 1000 to 2000 IU/kg significantly improved the lipid metabolism in the liver for grouper ( p  < .05).